2011
DOI: 10.1186/1479-5868-8-110
|View full text |Cite
|
Sign up to set email alerts
|

Hours spent and energy expended in physical activity domains: Results from The Tomorrow Project cohort in Alberta, Canada

Abstract: BackgroundKnowledge of adult activity patterns across domains of physical activity is essential for the planning of population-based strategies that will increase overall energy expenditure and reduce the risk of obesity and related chronic diseases. We describe domain-specific hours of activity and energy expended among participants in a prospective cohort in Alberta, Canada.MethodsThe Past Year Total Physical Activity Questionnaire was completed by 15,591 Tomorrow Project® participants, between 2001 and 2005… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 33 publications
0
41
0
Order By: Relevance
“…The gradual incorporation of nonexercise physical activities into daily occupational (31), transportation (32,33), and household routines could be the most feasible strategy for increasing energy expenditure for large numbers of individuals. Indeed, we observed that amongst those who are most active in the Tomorrow Project, nonleisuretime activities, primarily occupational, contributed the largest portions of energy expenditure to activity-related energy expenditure (34). Others have reported similar findings (35) and it has been suggested that nonexercise energy expenditure can vary by as much as 2000 kcal per day between individuals of similar weight (36).…”
Section: Discussionmentioning
confidence: 55%
“…The gradual incorporation of nonexercise physical activities into daily occupational (31), transportation (32,33), and household routines could be the most feasible strategy for increasing energy expenditure for large numbers of individuals. Indeed, we observed that amongst those who are most active in the Tomorrow Project, nonleisuretime activities, primarily occupational, contributed the largest portions of energy expenditure to activity-related energy expenditure (34). Others have reported similar findings (35) and it has been suggested that nonexercise energy expenditure can vary by as much as 2000 kcal per day between individuals of similar weight (36).…”
Section: Discussionmentioning
confidence: 55%
“…One challenge in understanding the effects of activity on health is that there is little consensus on how to assess activity in free-living people. Previous research on a subgroup of the ATP cohort has demonstrated relatively low levels of leisure-time activity compared with occupational and household activities ( 51 ) , and it has also been reported previously that ATP participants take part in insufficient leisure-time activity for cancer risk reduction ( 52 ) . Although the personal recommendation does not specify types of activity, the WCRF/AICR Panel did note that all forms of physical activity protect against some cancers.…”
Section: Discussionmentioning
confidence: 84%
“…Similarly, most physical activity questionnaires do not accurately assess the various work related activities typically involved in homemaking or work outside the home (24). Based on self-report, previous studies suggest that homemakers obtain less total physical activity (24), have lower overall activity-related energy expenditure (7), and are less likely to participate in vigorous leisure-time physical activity (25), than EW. A recent study conducted by the PEW Research Center found that stay-at-home mothers reported spending more time on childcare, housework, leisure activities, and sleep more than working mothers (6).…”
Section: Introductionmentioning
confidence: 99%